How does food choice motives relate to subjective well-being and loyalty? A cross-cultural comparison of vegan restaurant customers in South Korea and Singapore. Issue 2 (4th March 2022) - Lim, Kerri Ann; Ham, Sunny; Moon, Hye Young; Jang, Yoon Jung; Kim, Chang Sik
ABSTRACT: This study recruited 537 participants who dined at vegan eateries and posted images of their food on Instagram. Our sample included diners from 86 vegan eateries. An online questionnaire developed by Qualtrics was administered. This study explored the relationship between food choice motives, subjective well-being, and loyalty behavior among Singaporean and South Korean diners at vegan eateries. Findings from the PLS-SEM and multigroup analysis revealed that out of 9 health and non-health related food choice motive factors, mood, natural content, and health significantly affected subjective well-being, and perceived vitality was found to significantly affect customer loyalty at vegan eateries. Specifically, mood had significant effects on subjective well-being in South Korean vegan diners, while health, mood, and natural content significantly affected subjective well-being in Singaporeans vegan diners.